Pengaruh Penambahan Tongkol Jagung Terhadap Performa Pembakaran Bahan Bakar Briket Blotong (Filter Cake) - Hamidi, Nurkholis; Wardana, ING; Sasmito, Handono (Jurnal Rekayasa Mesin, 2011)
Studies have been carried out on utilizing agricultural wastes of corn cobs to enhance the properties of filter cake briquette. Briquettes of mixtures between filter cake and corn cobs were produced in order to increase the fiber content and reduce the ash content. In this study, the concentrations of corn cobs were varied at 0%, 2%, 6%, 10%, and 15%. The properties of the briquettes were compared. It was found that the burning rate, caloric value, burning temperature and combustion efficiency showed improvement with increase in corn cobs concentration. Keywords : filter cake, corn cobs, combustion performance